Jawabanmu

Jawaban paling cerdas!
2014-09-06T05:02:52+07:00
35). = (a log b^-1) (b log c^-1) (c log a^-1)
= (-1 a log b) . (-1 b log c) . (-1 c log a)
= (-1) . (-1) . (-1). a log b . b log c . c log a
= -1 . a log c . c log a
= -1 . a log a
= -1 . 1
= -1

36). = (2 log 5^1/2) + (2. 2^2 log 5) / 3 log 5 . 2 log 3
= (1/2 . 2 log 5) + (2 . 1/2 . 2 log 5) / (1 / (5 log 3)) (1 / (3 log 2))
= (1/2 . 2 log 5 + 2/2 . 2 log 5) / (1 / (5 log 2))
= 3/2 . 2 log 5 . 2 log 5
=

37). = 2 log 3 log 2 log x = 1
=> 2 log 2 = 1
=> 3 log 2 log x = 2
=> 3 log 9 = 2
=> 2 log x = 9
=> 2^9 = 512
=> x = 512

38). = (5 log 7 + 5 log 5 - 5 log 14 + 5 log 10) / (3 log 5 + 3 log 12 - 3 log 2 - 3 log 10)
= 5 log (7 . 5 : 14 . 10) / 3 log (5 . 12 : 2 : 10)
= 5 log 25 / 3 log 3
= 2 / 1
= 2

1 5 1